The Ovary Is an Alternative Site of Origin for High-Grade Serous Ovarian Cancer in Mice - Kim, Jaeyeon (Endocrinology, 2015)
Although named “ovarian cancer,” it has been unclear whether the cancer actually arises from the ovary, especially for high-grade serous carcinoma (HGSC), also known as high-grade serous ovarian cancer, the most common and deadliest ovarian cancer. In addition, the tumor suppressor p53 is the most frequently mutated gene in HGSC. However, whether mutated p53 can cause HGSC remains unknown. In this study, we bred a p53 mutation, p53(R172H), into conditional Dicer-Pten double-knockout (DKO) mice, a mouse model duplicating human HGSC, to generate triple-mutant (TKO) mice. Like DKO mice, these TKO mice develop metastatic HGSCs originating from the fallopian tube. Unlike DKO mice, however, even after fallopian tubes are removed in TKO mice, ovaries alone can develop metastatic HGSCs, indicating that a p53 mutation can drive HGSC arising from the ovary. To confirm this, we generated p53(R172H)-Pten double-mutant mice, one of the genetic control lines for TKO mice. As anticipated, these double-mutant mice also develop metastatic HGSCs from the ovary, verifying the HGSC-forming ability of ovaries with a p53 mutation. Our study therefore shows that ovaries harboring a p53 mutation, as well as fallopian tubes, can be a distinct tissue source of high-grade serous ovarian cancer in mice.